2019
DOI: 10.1016/j.livsci.2018.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet supplementation with clove and rosemary essential oils and protected oils (eugenol, thymol and vanillin) on animal performance, carcass characteristics, digestibility, and ingestive behavior activities for Nellore heifers finished in feedlot

Abstract: do Prado , Effects of diet supplementation with clove and rosemary essential oils and protected oils (eugenol, thymol and vanillin) on animal performance, carcass characteristics, digestibility, and ingestive behavior activities for Nellore heifers finished in feedlot,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 27 publications
3
27
0
7
Order By: Relevance
“…In a recent study by Al-Saht et al [ 61 ], using a blend of thymol and cinnamaldehyde, no effects on the rumen parameters and protozoa number were observed. Recently, De Souza et al [ 9 ] reported that the in situ digestibility values of DM, crude protein, and NDF were similar in heifers fed diets without or with a protected blend (4 g/animal/d) of essential oils (eugenol, thymol, and vanillin). The results of these studies are highly variable and dependent on various factors, such as the type of EO used in the blend, the rumen microbial community, pH, and the length of adaptation period to these EOs by the rumen bacteria [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study by Al-Saht et al [ 61 ], using a blend of thymol and cinnamaldehyde, no effects on the rumen parameters and protozoa number were observed. Recently, De Souza et al [ 9 ] reported that the in situ digestibility values of DM, crude protein, and NDF were similar in heifers fed diets without or with a protected blend (4 g/animal/d) of essential oils (eugenol, thymol, and vanillin). The results of these studies are highly variable and dependent on various factors, such as the type of EO used in the blend, the rumen microbial community, pH, and the length of adaptation period to these EOs by the rumen bacteria [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an in vivo study [ 8 ] demonstrated that the use of a blend of EOs (CRINA ® Ruminants), alone or combined with enzymes (amylases), can be an alternative to ionophore antibiotics to improve ruminal fermentation and the milk yield and quality of dairy cows. Similarly, positive results were obtained [ 9 ] using EOs (a blend of thymol, eugenol, and vanillin) as a potential substitute for antibiotics to improve cattle performance during the finishing phase. Among the various EOs studied, cinnamaldehyde, thymol, and eugenol are the most commonly used in animal feeds because of their well-reported antimicrobial properties [ 10 ].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the current study, the digestibility of DM and OM was greatly decreased by 400 mg/L thymol addition, which might indicate an inhibitory effect of a high dose of thymol on rumen nutrient digestion; this adverse effect was reported earlier by Cobellis et al [ 9 ]. Nevertheless, Vendramini et al [ 47 ] found no effect of an EO blend containing thymol on rumen DM digestibility when fed to lactating dairy cows, and an increase in DM apparent digestibility was reported by de Souza et al [ 48 ] after feeding heifers with an EO blend. These inconsistent results could be attributed to different conditions such as animal species and the composition of the EO applied in the different studies.…”
Section: Discussionmentioning
confidence: 99%